Thioctic acid shield against lipopolysaccharide depression and endoplasmic reticulum stress: GR7M/Homer/ATF6 signaling - Mai O. Kadry; Rehab M. Abdel-Megeed (Future Science OA, 2024)
Aim: Endoplasmic reticulum stress triggers neuronal unfolded protein accumulation, contributing to the pathophysiology of depression psychiatric illnesses.Materials & methods: The brain-derived neurotrophic factor (BDNF), metabotropic glutamate receptor type 7 (GRM7), phosphoinisitol kinase-3 (PIK3), serine/threonine kinase 1 (AKT) and Homer1 may afford an important signaling pathways in LPS induced depression rat model. Herein, thioctic acid, Burdock and propolis therapeutic index on lipopolysaccharide (LPS)-induced depression was monitored. BDNF/PI3K/GR7M/ATF6/CHOP/XBP/AKT/Homer-1 signaling pathways also opened a novel avenue in the integration of synaptic neurotransmission.Results: The aforementioned treatments elevated GR7M/BDNF/GABA gene expression meanwhile decreased reactive oxygen species generation (Malondialdehyde/glutathione reductase/Total antioxidant capacity) and reduced the expression of ATF6/CHOP/PI3K/AKT/XBP/Homer-1 post LPS elevation.Conclusion: Thioctic acid, propolis and Burdock are prospective therapeutic agents via GRM7/BDNF/AKT/PI3K/ATF6/XBP/homer -1 signaling pathways in LPS-induced depression.